Two Decades of Contemporary Surgery of Primary Cardiac Tumors - Jawad, Khalil; Owais, Tamer; Feder, Stefan; Lehmann, Sven; Misfeld, Martin; Garbade, Jens; Borger, Michael (The Surgery Journal, 2018)
Objective The decision to operate cardiac tumors is an issue of balancing surgical outcome and survival with quality of life (QOL). We report our single-center experience in managing primary cardiac tumors between 1994 and 2014.Methods and Results In this study, 269 patients were subjected to our standardized operative protocols, preoperative preparations, postoperative follow-up, and consents of participation. Demographic and preoperative/intraoperative/postoperative variables were collected with focus on long-term follow-up and survival. A total of 72,000 cardiac procedures were performed within 20 years at our institution. Two hundred sixty-nine patients were diagnosed with primary cardiac tumors (0.37%), with a male:female ratio of 1:1.68, mean age of 57.4 ± 19.5 years, and body mass index of 25.49 ± 6.5. The most presenting symptoms were dyspnea (n = 94), arrhythmias (n = 53), embolic event (n = 36), and chest pain (n = 29), and 33 patients were accidentally discovered. Isolated tumor excision and concomitant ablation were performed on 181 patients, while the rest needed additional procedures such as coronary artery bypass grafting (n = 27) or valve surgery (n = 61). Focus on pathology, tumor location was done reporting the commonest pathology such as myxoma (n = 177) and fibroelastoma (n = 56). The frequent site was the left atrium (n = 162). Our primary results showed incidence of bleeding in 9 patients (3.3%), arrhythmias in 76 patients (28.25%), and mortality in 49 patients (18.2%). Five patients (1.8%) showed recurrence and 220 patients (81.8%) showed complaint-free survival.Conclusion Complete excision of primary cardiac tumors is the golden rule in management as it improves survival and decreases morbidity expected from the progressing tumors process. The progression of minimally invasive techniques improves QOL and should be performed whenever possible.
Keywords: cardiac tumor; minimally invasive heart surgery; surgical outcome